PEMANFAATAN MEDIA CREATIVE CENTER DALAM PENGUATAN PROYEK PROFIL PELAJAR PANCASILA DI KOTA BANDUNG - Mulyanti, Mulyanti; Hidayati, Dian (Academy of Education Journal, 2023)
The independent curriculum rolled out by the Ministry of Education and Culture as the national curriculum is expected to be implemented optimally in 2025 for all stages in realizing students who have the character of a Pancasila student profile with six main characteristics: faith, fear of God Almighty, and have noble character, global diversity, mutual cooperation, independence, critical reasoning, and creative. In realizing this profile, it is implemented in project activities that are designed as creatively as possible and utilize the creative center media, namely the school's YouTube channel to provide meaningful experiences for students. The method used in this study is a descriptive qualitative approach with data sources obtained through interviews and observation. Interviews were conducted with two informants, namely MCC managers and educators. The observations made to students. The results showed that the existence of MCC greatly assisted schools and teachers in implementing activities to strengthen the Pancasila student profile project and increase student motivation.